System Shift and Stress Testing a Systems Reading Tool for Detecting Pre Shift Vulnerability in Complex Organizations - Raymond R. Tjandrawinata (International Journal of Social Service and Research, 2026)
Organizations invest significant resources in measuring how well they are performing. However, almost no investment is made in measuring how close they are to the conditions under which that performance collapses. This research argues that this gap is not accidental but rather a structural feature of measuring normal conditions, which is epistemologically blind to the dynamics that precede systemic transitions. Drawing on process ontology and the Systems Shift Framework, we develop a cross-domain stress testing methodology the Systems Shift Stress Testing Framework (SS-STF) oriented not so much on scenario simulation as on the interrogation of assumptions: identifying the structural conditions that hold a system in its current configuration, the thresholds at which those conditions fail, and the organization's current proximity to those thresholds. The framework was developed across three organizational domains manufacturing, finance, and human capital and integrated through a composite instrument, the Transition Proximity Index (TPI). Governance implications are outlined, including reframing stress testing as an epistemological obligation at the board level rather than a mere compliance exercise. This paper contributes to systems theory, the organizational resilience literature, and governance studies.